Sport and Art: Differences and Theatrical Similarities - Kosiewicz Jerzy (Sciendo, 2014)
A certain tradition of philosophical considerations on the interrelation between sport and art has already been established. According to Tim L. Elcombe (Elcombe, 2012, p. 201), such considerations on the subject first appeared in English-language literature in the 1970s and 1980s, and were fruitful. Usually, they appear together with questions on the aesthetic properties of sport - in this case, a special issue of the Journal of the Philosophy of Sport dedicated to -Sport and Aesthetics‖ (2012, vol. 39, no. 2), and an excellent postdoctoral dissertation by Jakub Mosz entitled -Estetyczne aspekty uczestnictwa w sporcie‖ (English: Aesthetic aspects of participation in sports) may serve as good examples. In his article (Elcombe, 2012), Tim L. Elcombe describes the contention and briefly characterizes the main differences between the two opposing viewpoints (Elcombe, 2012, pp. 202-204). It should be noted that he sympathizes with the view of David Best, who some years ago argued that sport is not art (1988, pp. 527-539). He believes that -although art could use sport as a subject, art could not be the subject of sport‖ (Elcombe, 2012, p. 202). I would like to make that statement more specific by adding that its second part suggests that the display of artistic values cannot be the fundamental purpose of sport. I shall expand on that later. Best's viewpoint was criticized by Jan Boxil (1988), Spencer Wertz (1988), and Terry Roberts (1995), who believed that sport could be treated as art. Christopher Cordner (1995a; 1995b) and Joseph Kupfer (1988) also challenged Best, although they did not entirely disagree with him (see: Elcombe, 2012, pp. 202-204). Because literature on the subject published in English presents diversified statements on the interrelation between sport and art, and the circle of people engaged in the matters of physical culture in Poland is still in favor of equating sport with art, I have decided to present my own stance on that matter.